Orthopedic therapeutic surgery for bone metastasis of liver cancer: Clinical efficacy and prognostic factors - Lian, Qiujian; Liu, Chang; Chen, Fengmei; Wang, Bingxuan; Wang, Miao; Qiao, Suchi; Guan, Zhengmao; Jiang, Shuai; Wang, Zhiwei (Frontiers in Surgery, 2022)
Objectives: To investigate the clinical efficacy of orthopedic therapeutic surgery (OTS) in patients with bone metastasis of liver cancer, and explore the prognostic factors. Methods: The electronic medical records of patients with bone metastasis of liver cancer in the Third Affiliated Hospital of Naval Medical University from September 2016 to August 2021 were retrospectively collected. A total of 53 patients were included. Patients were assigned to the OTS (n=35) or the control group (n=18) based on receiving orthopedic therapeutic surgery or conservative treatment. The pre/post-treatment Karnofsky performance status scale (KPS) and numeric rating scale (NRS) scores were compared. Univariate and multivariate Cox regression analyses were used to explore the prognostic factors affecting survival after bone metastasis. Logistic regression analyses were adopted to discover potential factors that contributed to greater KPS score improvement. Results: The axial bone accounted for 69.8% of all bone metastases. The proportion of multiple bone metastases was 52.8%. After surgery, the median KPS score of the OTS group increased from 60 to 80 (p < 0.001), and the median increase in the OTS group was higher than that of the control group (p = 0.033). The median NRS score of the OTS group declined from 6 to 2 after surgery (p < 0.001), and the median decline in the OTS group was higher (p = 0.001). The median survival was 10 months in the OTS group versus 6 months in the control group (p < 0.001). Higher pre-treatment KPS scores, undergoing liver primary lesion surgery, and undergoing orthopedic therapeutic surgery were protective factors of survival. Undergoing orthopedic therapeutic surgery was of great help to improve the KPS score. Conclusions: Orthopedic therapeutic surgery for bone metastasis of liver cancer provides benefits to the quality of life. Patients who have their primary liver lesions removed, undergo orthopedic therapeutic surgery, and have a better physical condition before treatment tend to have longer survival.